Analysis of Learning Motivation Based on the POE (Predict-Observe-Explain) Learning Model in Science Education - Edres, Bunga; Azizahwati; Futra, Dedi (Universitas Negeri Yogyakarta, 2025)
Learning motivation is an important factor in science learning, but it is still uneven among students. The particular study aimed to analyze the increase in student learning motivation after applying the Predict-Observe-Explain (POE) learning model compared to conventional methods. The method used descriptive quantitative with a structured survey technique. The subjects were seventh-grade students of MTs Darul Falah Langgam in the 2024/2025 school year. The sample was selected using a purposive sampling technique, consisting of 48 students, who were divided into two classes, namely VII A and VII B, each totaling 24 students. The research instrument was a questionnaire consisting of 30 questions with six indicators of learning motivation. The results showed that the POE learning model was more effective in increasing learning motivation than conventional methods. Students’ learning motivation in classes using the POE model increased by 68% (high category), meanwhile conventional methods increased by 58% (medium category). This finding indicates that the POE approach create a more interesting learning experience, increase student engagement, and help them understand concepts more deeply through the stages of prediction, observation, and explanation.